Pendampingan Pembuatan Keripik Jenang Dumbleg Berbahan Dasar Jenang Dumbleg di Kecamatan Gondang Kabupaten Nganjuk - Afiyah, Dyah Nurul; Sarbini, Riska Nurtantyo; Daroini, Ahsin (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
Jenang dumbleg is one type of wet food that have storage duration was very short so its often to producers have to losses their products not sold off quickly .We need to the processing continuation of this product to of increasing age to keep from jenang dumbleg, traditional foods typical kecamatan gondang kabupaten nganjuk .One processing that easy and a lot of favored consumers is made it into the shape of chips .The activity was done in 4 stage, namely socialization to producers, skills training about processing jenang dumbleg, skills training the procedure of making jenang dumbleg chips, skills training about the technology packaging. The outcome of the activities can be seen that producers can make jenang dumbleg that good and were it being flaky jenang dumbleg having the value organoleptik good and acceptable for consumers.